Local feed resources for poultry - Leenstra F. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
In poultry ‘no input’, ‘low input’ and commercial production can be distinguished. ‘No input’ implies scavenging poultry with some kitchen waste or crop residues as supplemental feed. Input is negligible and economic efficiency is high, provided there is any output. Commercial production is capital intensive and completely based on supplied feed. Birds might be given outside access for foraging, but this is for behavioural and welfare reasons, not for nutrition. Chickens are real omnivores. The feed industry utilizes all kinds of ingredients and by-products for least cost rations. Literature provides a tremendous amount of information on feeding value of a wide variety of feed ingredients. Low input systems are a difficult category for economic evaluation. Birds often have to get part of their diet from scavenging, but also receive on a regular basis (compound) feed. This can be home-made from local resources or industrial and thus out-ofpocket costs. Purchase of feed is only possible if sufficient income can be generated from sales of eggs or birds. Lack of market access (buying resources and selling products) and competition from industrially produced eggs and meat are more a barrier than knowledge on feed resources. With regard to management no input and low input systems have a tendency to ‘over-graze’ the resources for scavengers, with high mortality and low productivity as a consequence. Reducing numbers of birds might increase productivity.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)